2014
DOI: 10.1002/art.38244
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Ankylosing Spondylitis Is Associated With the Brain Networks of Sensory Salience and Attention

Abstract: Objective. Fatigue is one of the cardinal features of ankylosing spondylitis (AS) and contributes substantially to the disability associated with this disease. The mechanisms underlying fatigue in AS remain poorly understood, and this has hampered the development of targeted, effective treatment of this disabling feature of AS. The current study was undertaken, therefore, to investigate the brain networks underlying fatigue in AS.Methods. Twenty patients with back pain secondary to AS (15 men and 5 women; mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…Coincidentally, a recent study of a patient with right MFG resection clarified that right MFG was a crucial node of attentional circuits, and it controlled over both ventral and dorsal attention networks . What's more, some evidence has already illuminated that attention deficit may be related to the presence of fatigue . For example, Jau‐Shin Lou et al reported PD patients with fatigue had abnormal attention network compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coincidentally, a recent study of a patient with right MFG resection clarified that right MFG was a crucial node of attentional circuits, and it controlled over both ventral and dorsal attention networks . What's more, some evidence has already illuminated that attention deficit may be related to the presence of fatigue . For example, Jau‐Shin Lou et al reported PD patients with fatigue had abnormal attention network compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jau‐Shin Lou et al reported PD patients with fatigue had abnormal attention network compared with controls. Moreover, Qi Wu et al revealed fatigue in ankylosing spondylitis patients were correlated with the dorsal and ventral attention networks. In this study, the results of decreased ALFF in right MFG and altered FC between right MFG and right middle temporal gyrus and left superior parietal gyrus further suggested that impaired attention network was likely involved in fatigue of PD.…”
Section: Discussionmentioning
confidence: 99%
“…19 The PCS (range 0-52 31 and the 40-item 6-point scale AIM 8 were used to assess the cognitive/affective functions as previously described. 40 The painDETECT Questionnaire 11 was used to determine the neuropathic component of AS pain.…”
Section: Clinical and Psychophysical Assessments And Brain Imagingmentioning
confidence: 99%
“…Previous studies report a considerable residual fatigue in patients with AS after treatment with TNFi 37 regardless of the amount of pain relief. 26 Our recent brain imaging investigation of the central mechanism of fatigue in AS indicates that pain and fatigue have differential effects on the brain; fatigue more strongly impacting motor and attentional networks 40 than areas more classically implicated in pain perception. 7 The aim of this study was to examine the differential effect of TNFi treatment on symptom relief in patients with AS with focus on pain and fatigue.…”
Section: Introductionmentioning
confidence: 98%
“…The cytokines alter the metabolism of neurotransmitters serotonin [ 27 , 28 ], dopamine [ 28 31 ], glutamate [ 32 , 33 ], which in turn leads to decreased production of the trophic or growth factors necessary for neurogenesis and neuroplasticity [ 6 , 34 , 35 ], or norepinephrine [ 5 , 6 ]. Many studies demonstrated reduction of brain matter, especially in hippocampus [ 19 , 35 37 ], but also different alterations in other areas of the brain [ 38 43 ] under continuously elevated IL, or changes in functional connectivity [ 43 48 ]. The latter can best be encompassed by functional neuroimaging methods and will be discussed in a separate section.…”
Section: Peripheral-to-central Communicationmentioning
confidence: 99%